The peculiar characteristics and advancement in diagnostic methodologies of influenza A virus - Raza, Muhammad Asif; Ashraf, Muhammad Awais; Amjad, Muhammad Nabeel; Din, Ghayyas Ud; Shen, Bei; Hu, Yihong (Frontiers in Microbiology, 2025)
Influenza A virus (IAV) is a significant public health concern, causing seasonal outbreaks and occasional pandemics. These outbreaks result from changes in the virus’s surface proteins which include hemagglutinin and neuraminidase. Influenza A virus has a vast reservoir, including wild birds, pigs, horses, domestic and marine animals. It has over 130 subtypes based on differences in hemagglutinin and neuraminidase protein. IAV affects all age groups but impacts young children more especially during the colder season. Despite the development of vaccines and antiviral drugs, IAV is still a major cause of respiratory illnesses and deaths. Surveillance of IAV is crucial to detect new strains and assess vaccine effectiveness. Detection of IAV relies on methods like hemagglutination assay, PCR, cell culturing, and immunochromatography-based tests. Precise and early detection of IAV strain is crucial for quick treatment using antiviral drugs and unraveling epidemiological patterns to curb epidemics and pandemics on time. Advancements in diagnostic methodologies have enabled us to detect the IAV at early stages by overcoming the limitations of previously used diagnostic tests, further preparing us to combat future epidemics more effectively. This review article discusses the traditional and advanced diagnosis methods for detecting IAV.